ChemInform Abstract: PhI(OAc)2‐Mediated Functionalization of Unactivated Alkenes for the Synthesis of Pyrazoline and Isoxazoline Derivatives. Issue 28 (July 2015) - Hu, Xiao‐Qiang; Feng, Guoqiang; Chen, Jia‐Rong; Yan, Dong‐Mei; Zhao, Quan‐Qing; Wei, Qiang; Xiao, Wen‐Jing
Abstract Optimal conditions are developed for the radical cyclization of β, γ‐unsaturated hydrazones and oximes to afford pyrazolines and isoxazolines.